PERSENTASE KARKAS, DAGING, DAN KULIT DOMBA EKOR TIPIS JANTAN PADA UMUR DAN BOBOT POTONG YANG BERBEDA - , FIQRA YUDA ADAM, Dr. Ir. Setiyono, SU ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The experiment was aimed to evaluate the effect of age and slaughter weight on the carcass, meat and hide percentages. This experiment was used 60 thin tailed ram. Before slaughtering, the thin tailed ram were devided into two groups based on their age (less than one year age and above one to two years age). Each groups are devided two slaughter weights, weight I (15-20 kg) and weight II (20.5-25 kg). Special bracelets were used as identifier tools. Data were analyzed using CRD factorial of 2x2 (2 groups based on age, 2 groups bases on slaughter weight). The results showed that the higher level of slaughter weight affected the carcass and meat which is seemed on the increasing percentage of carcass and meat of the ram (P<0.05). However, the age were not seemed affect on the percentage of carcass and hide of the ram. In conclusion, there was no interaction between age and slaughter weight with percentage of carcass, percentage of meat and percentage of hide.